THE INFLUENCE OF THE HYDROGEN INJECTION PARAMETERS ON THE COMBUSTION PROCESS OF IC ENGINE - Grujic, Ivan; Stojanovic, Nadica; Petrovic, Miroslav (Acta Technica Corvininesis, 2023)
First obstacle is the potential of the production of the electric energy, necessary for the supply and charge of the electric vehicle batteries, as well as necessary infrastructure for this. [...]is the recycling of the batteries materials. The main advantage of the hydrogen is its chemical composition, that is, the hydrogen doesn't have carbon in its chemical composition, how the other fuels have. Because of the mentioned, many researchers work on the subject of hydrogen use as the fuel for IC engines. By considering many factors such are trend of mitigating climate change worldwide, the contribution of a widespread, reliable and affordable propulsion technology like the IC engine is, it can be said that the future use of IC engines can be very significant, once when the usage of conventional fuels reduces, with the increased use of alternative fuels such is hydrogen. First of all, during the Test 1 (injection during the intake stroke), it was very hard to start engine with this approach.